Crop Management System Based on Digital Technologies - Zakirova A.R. (EDP Sciences, 2021)
Crop farming is one of the most important branches of agriculture that ensures the food security of the country. For crop farming development, it is necessary to solve the problems of reducing the quantity and quality of the resulting crop due to insufficient nutrition and care, untimely harvesting and improper storage. To increase the efficiency and sustainability of the industry, it is necessary to digitalize both the production systems and decision-making processes at all levels of management. The study considers the stages of a digital crop management system: accounting for acreage with an electronic field map; organization of crop rotation taking into account organizational, soil-climatic and economic aspects of production; monitoring of technological operations; control of agricultural machinery with the formation of primary documents for accounting for completed works; maintaining a subsystem of material resources using the technic of precision farming; filling in technological maps and accounting for actually completed works with a list of works, the composition of agricultural aggregates, the timing of operations, production rates and fuel consumption, the need for seeds, fertilizers, plant protection products, and the cost of resources. The increased attention to the problem of digital agriculture on the part of the state and the highly competitive environment promote the use of new technological mechanisms and methods of work by agricultural producers, which are based on the use of Internet technologies, satellite navigation, robotics, sensors and sensors, and unmanned vehicles. Digitalization of agricultural processes allows increasing crop productivity, the efficiency of using material resources, equipment and human potential.